The Effect of Ankle Pumping on the Changes of ABI Value in Diabetic Neuropathic Patients - Awaluddin Awaluddin; Sugiyanto Sugiyanto (Jurnal Keperawatan, 2022)
Introduction: Diabetes mellitus is a serious disease and is commonly known as the “mother of disease” because this disease can be a risk factor for various other diseases of the body organs. Some of the consequences of diabetes are an increased risk of hypertension, heart disease, stroke, retinopathy, including diabetic neuropathy. Diabetic neuropathy is a type of nerve damage that occurs due to diabetes. One of the non-pharmacological interventions is ankle pumping. Objectives: This study aimed to analyze the effect of ankle pumping on changes in ABI values ​​in diabetic neuropathy patients. Methods: This research comprised a Quasi-experimental research design with one group pretest-posttest—a total of 69 respondents were taken using the total sampling technique. Ankle pumping intervention is given to diabetic neuropathy patients at Massenrampulu Hospital in June-August 2020, two times a day for three consecutive days (@ 15 minutes). Results: From this study, the majority of respondents were seniors (n=31, 44.9%), female (n=42, 60.9%). Before the intervention, most respondents (68.1%) showed an abnormal ABI value at <0.90 for 47. Furthermore, after the intervention, more than half of respondents (69.6%) were on Borderline 0.91-0.99 for 48. The Wilcoxon test results significantly affect the ABI value before and after the intervention with a sig value of p = 0.003. Conclusions: There is a significant effect of ankle pumping therapy on changes/increases in ABI values ​​in type-2 DM patients with neuropathy at Massenrempulu General Hospital, Enrekang District.